Slaying the Serpent (The Biblical archaeology review, 2024)
A stamp seal excavated in 2022 by the Selz Foundation Hazor Excavations in northern Israel, under the direction of Igor Kreimerman and the late Amnon Ben-Tor, offers a tantalizing glimpse of a widespread mythological theme: the battle between a hero and a seven-headed serpent. This motif is attested throughout the ancient Near East and eastern […]